Pengaruh Kesejahteraan Karyawan Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada Pdam Tirta Manakarra Kabupaten Mamuju - Mayang; Halim, Agus (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Employee welfare is a strategic factor in improving employee performance, both directly and indirectly through job satisfaction. This study aims to analyze the effect of employee welfare on employee performance, with job satisfaction as a mediating variable at PDAM Tirta Manakarra, Mamuju Regency. This research employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to employees of PDAM Tirta Manakarra, Mamuju Regency, and analyzed using path analysis through the Structural Equation Modeling (SEM) approach. The results indicate that employee welfare has a positive and significant effect on job satisfaction and employee performance. Furthermore, job satisfaction has a positive and significant effect on employee performance. The findings also reveal that job satisfaction mediates the relationship between employee welfare and employee performance. Therefore, improving employee welfare supported by high levels of job satisfaction can optimally enhance employee performance. This study is expected to serve as a reference for the management of PDAM Tirta Manakarra, Mamuju Regency, in formulating sustainable employee welfare and human resource management policies.